L2 pragmatic comprehension of aural sarcasm: Tone, context, and literal meaning. (April 2022) - Koh, Joanne (Won-Young); Lee, Sineun; Lee, Josephine Mijin
Abstract: L2 pragmatics is an expanding field but research on pragmatic comprehension—particularly comprehension of aural sarcasm—remains relatively scant. This study thereby examines L2 learners' accuracy and speed in interpreting auditory sarcasm and seeks to unpack the cues that affect their comprehension success. Fifty-one intermediate and advanced Korean EFL learners had their comprehension of English sarcasm assessed by completing a multimedia pragmatic listening test. By replicating Voyer and Vu's (2016) design, the test items were varied according to the type of literal meaning (positive/negative), context (positive/negative), and intonation (sincere/sarcastic). The results indicate that both proficiency level groups responded more accurately and quickly to congruent pairs (i.e., negative context with a sarcastic tone or positive context with sincere tone) than incongruent pairs (i.e., positive context with a sarcastic tone or negative context with sincere tone). A proficiency effect was evident where advanced learners were more accurate but not necessarily faster than intermediate learners. In terms of literal meaning, both proficiency level groups were significantly more accurate and faster at responding to positive literal meaning. Lastly, an interaction effect was present among literal meaning, congruency, and proficiency, highlighting the interplay of context, intonation, and literal meaning in comprehending L2 sarcasm across different L2 proficiency levels.